(untitled) (Global Journal of Management and Business Research, 2015)
With the rapid development of telecommunication industry and usage rates of mobile phone users in Bangladesh truly it is significant to know whether the customers are satisfied with the service of their operator or how the operators think to provide better service to attract its valued customers. In this study, we have examined the determinants of customer satisfaction and loyalty conditions of Grameenphone to recommend what service factors could be applied strategically to sustain the leadership over the telecom industry in Bangladesh. The findings confirm that customer satisfaction and loyalty would be enhanced if the operator emphasis on core service factors like service quality, brand image, service charges, network quality and Value Added Services (VAS) etc. For this the study is conducted on 150 Grameenphone subscribers in Bangladesh. The Chi-square test for customer satisfaction factors and customer loyalty factors suggests that GP’s customers are satisfied with their services but 40% of them still are not willing to subscribe about GP to other potential users. On the basis of the findings, the study concludes by recommending some potential service factors that could be helpful for GP to gain the competitive advantage and will create a positive impact over customer’s mind about receiving GP’s service.